2015
DOI: 10.1007/s11605-015-2835-y
|View full text |Cite|
|
Sign up to set email alerts
|

Impact Total Psoas Volume on Short- and Long-Term Outcomes in Patients Undergoing Curative Resection for Pancreatic Adenocarcinoma: a New Tool to Assess Sarcopenia

Abstract: Background While sarcopenia is typically defined using total psoas area (TPA), characterizing sarcopenia using only a single axial cross-sectional image may be inadequate. We sought to evaluate total psoas volume (TPV) as a new tool to define sarcopenia and compare patient outcomes relative to TPA and TPV. Method Sarcopenia was assessed in 763 patients who underwent pancreatectomy for pancreatic adenocarcinoma between 1996 and 2014. It was defined as the TPA and TPV in the lowest sex-specific quartile. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
228
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(235 citation statements)
references
References 60 publications
3
228
2
2
Order By: Relevance
“…HGS would have a great advantage to select patients with good performance status but high risk for morbidity. Previous studies for other upper abdominal surgery such as hepatocellular carcinoma, pancreas cancer, and metastatic liver tumor demonstrated that sarcopenia was a risk factor for postoperative complication [12,35,36]. However, no report showed a correlation of sarcopenia and respiratory complications, which is different from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…HGS would have a great advantage to select patients with good performance status but high risk for morbidity. Previous studies for other upper abdominal surgery such as hepatocellular carcinoma, pancreas cancer, and metastatic liver tumor demonstrated that sarcopenia was a risk factor for postoperative complication [12,35,36]. However, no report showed a correlation of sarcopenia and respiratory complications, which is different from the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Although in some studies a correlation between PA and post‐operative complications was seen, the majority have failed to prove a relationship between PA‐assessed sarcopenia and survival 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23. Only few have actually assessed the agreement between PA and SMA within their population; Jones et al studied 100 patients with colorectal cancer and reported a Spearman correlation of 0.8 for PA and SMA and a Spearman correlation of 0.94 for PA and PLW, which could not be reproduced in our cohort 11.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used to predict surgical complications in different cancer types with contrasting results. PA has shown a correlation with post‐operative complications in individual studies on colorectal cancer, colorectal liver metastases, kidney cancer, bladder cancer, cholangiocarcinoma, and hepatocellular cancer,11, 12, 13, 14, 15, 16 while this effect was not seen in other pancreatic cancer, endometrial cancer, biliary cancer, or sarcoma studies 17, 18, 19, 20. Interestingly, only few cancer studies were able to show a correlation between PA and survival 21, 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…The next best option is to use data from multiple studies using percentile based summative values. The literature currently uses a plethora of cohort-specific values, including using the lowest median, tertile, quartile, quintile, or standard deviation (19)(20)(21)23,24,27,28,(33)(34)(35)(36)(37)(38) in the study cohort. We validated our cohort's cutoff, by performing ROC curve analysis with regards to acute radiotoxicities which correlates to approximately a TPA of 500.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the association between pre-operative and post-operative TPA with outcomes in patients with pancreatic cancer (19)(20)(21)(22)(23)(24)(25). However, none have examined TPA prior to neoadjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%